POLLUTER PAYS PRINCIPLE DALAM PERSPEKTIF HUKUM PIDANA - Sipayung, Oktaviani br; Ismanyah, Ismanyah (UNES Law Review, 2023)
Human activities are often the main cause of environmental damage and pollution. Therefore, a law that is in favor of environmental protection is needed to maintain the preservation and sustainability of the environment. The polluter pays principle requires that every business actors that causes pollution or damage to the environment bears all costs incurred in the context of environmental restoration. In order to guarantee the implementation of good environmental protection and management, criminal law enforcement plays an important role. Criminal law can influence business actors so that the business decisions they make do not damage or pollute the environment. This research was conducted to answer how the regulation and application of the polluter pays principle in UUPPLH and how the polluter pays principle when viewed from the perspective of criminal law. This research was conducted using normative research methods with the data source being positive law sources in Indonesia. The polluter pays principle is not explicitly regulated in UUPPLH to be applied in handling criminal acts, because this principle takes precedence in enforcing administrative law through instruments environmental economics and civil law through environmental dispute lawsuits and is closely related to the concept of strict liability in calculating the compensation that must be borne by the perpetrators of environmental pollution and/or damage. The existence of an additional penalty in the form of "remedial action as a result of a crime" that can be imposed on corporations that pollute and/or damage the environment is a gap in the implementation of the polluter pays principle through criminal law enforcement.